2017
DOI: 10.1049/iet-net.2017.0021
|View full text |Cite
|
Sign up to set email alerts
|

Trust management for reliable decision making among social objects in the Social Internet of Things

Abstract: The Internet is populated with billions of electronic gadgets that have become a part of our fabric. Internet of Things is gaining popularity in at most all applications from smart buildings, intelligent transportation, healthcare and defence. IoT is a many vision one paradigm technology. One of the many visions of IoT is to make 'Things' social. Social Internet of Things (SIoT) is a young paradigm that integrates IoT and Social networking principles where Things are not only autonomous and smarter but also so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 17 publications
0
21
1
Order By: Relevance
“…Community Interest. Community interest is an important factor that empowers trust and interaction between objects of the same community [34]. Community interest and culture could highly affect how individuals make their decisions.…”
Section: Social Influence-related Factorsmentioning
confidence: 99%
“…Community Interest. Community interest is an important factor that empowers trust and interaction between objects of the same community [34]. Community interest and culture could highly affect how individuals make their decisions.…”
Section: Social Influence-related Factorsmentioning
confidence: 99%
“…Here, quality of service was considered, including delivery ratio, measurement of packet ratio (forward and delivery), and consumed energy between sensors, which allowed people to compute the trust level among social networks and boost the level of social relationships among owners and devices [24]. Saied et al [35] suggested a scheme that is fully based on security. This scheme works as a shield against attacks.…”
Section: Current State Of the Art In Peer-to-peer And Client/server Nmentioning
confidence: 99%
“…Chen, Bao [24] Nitti, Atzori [14] Ben Saied, OLIVEREAU [35] Chen, Chang [34] Figure 7 describes the classified catalog of trust-and friendliness-based approaches in the social IoT.…”
Section: Relations Between Objectsmentioning
confidence: 99%
See 2 more Smart Citations